The great Maya droughts in cultural context: case studies in resilience and vulnerability - Iannone, Gyles, editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2014)
In The Great Maya Droughts in Cultural Context, contributors reject the popularized link between societal collapse and drought in Maya civilization, arguing that a series of periodic collapses," including the infamous Terminal Classic collapse (AD 750-1050), were not caused solely by climate change-related droughts but by a combination of other social, political, and environmental factors. New and senior scholars of archaeology and environmental science explore the timing and intensity of droughts and provide a nuanced understanding of socio-ecological dynamics, with specific reference to what makes communities resilient or vulnerable when faced with environmental change. Contributors recognize the existence of four droughts that correlate with periods of demographic and political decline and identify a variety of concurrent political and social issues. They argue that these primary underlying factors were exacerbated by drought conditions and ultimately led to societal transitions that were by no means uniform across various sites and subregions. They also deconstruct the concept of "collapse" itself--although the line of Maya kings ended with the Terminal Classic collapse, the Maya people and their civilization survived. The Great Maya Droughts in Cultural Context offers new insights into the complicated series of events that impacted the decline of Maya civilization. This significant contribution to our increasingly comprehensive understanding of ancient Maya culture will be of interest to students and scholars of archaeology, anthropology, geography, and environmental studies.--Provided by publisher.
Introduction: Resilience, vulnerability, and the study of socioecological dynamics / Gyles Iannone -- The dynamics of ancient Maya developmental history / James Aimers and Gyles Iannone -- Assessing the great Maya droughts: some critical issues / Gyles Iannone, Jason Yaeger, and David Hodell -- Agricultural landscapes, deforestation, and drought severity / Robert Griffin, Robert Oglesby, Thomas Sever, and Udaysankar Nair -- Climate change in the ancient Maya forest: resilience and adaptive management across millennia / Anabel Ford and Ronald Nigh -- The end of the beginning: drought, environmental change, and the Preclassic to Classic transition in the east-central Maya lowlands / Nicholas Dunning, David Wahl, Timothy Beach, John Jones, Sheryl Luzzadder-Beach, and Carmen McCane -- A tale of three cities: effects of the AD 536 event in the lowland Maya heartland / Bruce H. Dahlin and Arlen F. Chase -- Collapse without drought: warfare, settlement, ecology, and site abandonment in the Middle Pasion region / Matt O'Mansky -- The Classic Maya collapse, water, and economic change in Mesoamerica: critique and alternatives from the "wet zone" / Arthur A. Demarest -- Water in the West: chronology and collapse of the Classic Maya river kingdoms / Andrew K. Scherer and Charles Golden -- Oxygen isotopes from Maya archaeological deer remains: experiments in tracing droughts using bones / Antoine Repussard, Henry P. Schwarcz, Kitty F. Emery, and Erin Kennedy Thornton -- The prehistoric Maya of northern Belize: issues of drought and cultural transformations / Fred Valdez and Vernon Scarborough -- An archaeological consideration of long-term socioecological dynamics on the Vaca Plateau, Belize / Gyles Iannone, Arlen F. Chase, Diane Z. Chase, Jaime Awe, Holley Moyes, George Brook, Jason Polk, James Webster, and James Conolly -- Tracking climate change in the ancient Maya world through zooarchaeological habitat analyses / Kitty F. Emery and Erin Kennedy Thornton -- Maya drought and niche inheritance / David Webster.
Keywords: Mayas -- History; Mayas -- Social conditions; Mayas -- Antiquities; Droughts -- Central America -- History; Indigenous peoples -- Ecology -- Central America; Human beings -- Effect of climate on -- Central America; Crops -- Central America -- Effect of drougt on; Environmental archaeology -- Central America; Social archaeology -- Central America; Central America -- Antiquities